Kinetic Study of Liquid-Phase Glycerol Hydrodeoxygenation into 1,2-Propanediol over CuPd/TiO2‑Na (2023)
Hydrodeoxygenation (HDO) kinetics of glycerol into 1,2-propanediol (1,2-PDO) in the liquid phase is studied on Cu-Pd/TiO2 catalysts. At a stirring speed higher than 480 rpm and an average diameter of the catalyst particles smaller than 89.5 μm, no mass transfer resistance artifacts are observed. The increasing temperature and H2 concentration promote the glycerol conversion and the selectivity to 1,2-PDO and disfavor the selectivity to acetol. Based on the experimental data, empirical kinetic pseudo-homogeneous expressions are proposed for glycerol disappearance, 1,2-PDO formation, and acetol formation in the catalytic system. Dependence of the disappearance rate of glycerol is closer to 1 with respect to glycerol and nonmeaningful with respect to H2. The formation rate of 1,2-PDO is not highly dependent on the initial concentration of glycerol or H2, and the formation rate of acetol is directly dependent on glycerol and inversely dependent on H2, since it accelerates acetol conversion to 1,2- PDO. The activation energies for glycerol disappearance (77.8 kJ/mol), 1,2-PDOformation (51.2 kJ/mol), and acetol formation (84.6 kJ/mol) evidenced the selective formation of 1,2-PDO in this catalytic system.